Optimization of stocking density of Labeo rohita and Cirrhinus mrigala spawn in relation to water quality, survival and growth under recirculating system - SHARMA, JAI GOPAL; KUMAR, SUNIL; CHAKRABARTI, RINA (The Indian Journal of Animal Sciences, 2014)
The effect of stocking density on the survival and growth of Labeo rohita (rohu) and Cirrhinus mrigala (mrigal) was evaluated under recirculating systems. Indian major carp rohu (1.0±0.002 mg) and mrigal (1.0±0.002 mg) spawns were cultured separately at 3 different stocking densities of 100, 125 and 150 larvae 15 litre aquarium. Survival was significantly (P<0.001) higher in the 100 and 125/ quarium densities than the 150 larvae/aquarium system for both rohu and mrigal. Maximum final average weight (rohu: 35. 17±0.27 mg; mrigal: 30.38±0.31 mg) was obtained in the 100 larvae/aquarium treatment. Food was most efficiently utilized in the low density system was evident from the lower values of feed conversion ratios (rohu: 1.75±0.001; mrigal: 2.04±0.002). Specific growth rate was also maximum (rohu: 5.15±0.011; mrigal 4.94±0.01) in 100 larvae/ aquarium density. In the experiment with rohu, dissolved oxygen level was significantly. higher in the low density (5.44:1:0.07 mg/l) followed by 125 and 150 larvae!aquarium densities. Values of ammonia, phosphate and chemical oxygen demand were minimum in 100 larvae/ aquarium density system. In case of mrigal, though there was no significant difference between 100 and 125 larvae/ aquarium densities, for dissolved oxygen and ammonia but nitrite, phosphate and chemical oxygen demand were significantly (P<0.05) lower in the former than the latter, 150 larvae/ aquarium density system significantly varied from other 2 systems for these water quality parameters. Effects of stocking density has been reflected on water quality which in turn intluences the performance of carp spawn.